PERDAGANGAN SAHAM DALAM ISLAM - Suprihatin . (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2002)
Trade of exchange is something contemporary that had never been identified in the age of Rasulullah, of sahabat, or of Tabi’in. where is the position of trade of exchange in Islamic Law? This is issue will be discussed in this moment